Multi-modality Imaging Evaluation of a Rare and Complex Case of Single Ventricle Physiology; the important role of Cardiac MR - Mantini, Cesare; Mastrodicasa, Domenico; Di Mascio, Valeria; Procaccini, Luca; Olivieri, Marzia; Scarano, Michele; Ricci, Fabrizio; Cademartiri, Filippo (Acta Biomedica Atenei Parmensis, 2022)
Congenital heart diseases (CHD) represent a major clinical and diagnostic challenge for correct abnormality identification and subsequent successful therapy; even more challenging is following-up patient health after multiple post-interventional corrections often required in complex cardio-vascular abnormalities. We describe a multi-modality imaging evaluation of a complex congenital cardio-vascular diseases, underlining the relevance of cardiac magnetic resonance to non invasively solve some issues related to postsurgical changes.